Current antipsychotic agent use and risk of venous thromboembolism and pulmonary embolism: a systematic review and meta-analysis of observational studies - Yinzhao Liu; Jun Xu; Kacey Fang; Yue Xu; Ju Gao; Chao Zhou; Xiaowei Tang; Xinyu Fang; Jiu Chen; Chunming Xie; Fuquan Zhang; Xiangrong Zhang; et al. (SAGE Publishing, 2021)
Background: Antipsychotic agents (APS) are widely used drugs to treat psychotic symptoms and can effectively reduce both positive and negative symptoms of schizophrenia. For decades, some studies suggested that there is a relationship between using APS and the risk of venous thromboembolism (VTE) and pulmonary embolism (PE). However, results remain inconclusive. Method: This review has been registered in International Prospective Register of Systematic Reviews (PROSPERO, ID: CDR42020155620). Relevant studies were identified among observational studies published up to 1 October 2019 in the databases MEDLINE, EMBASE, and Cochrane Library. Random or fixed-effects models were used to calculate the pooled odds ratio (OR). Results: In total, 28 observational studies were included. The results showed that compared with non-users, current APS users have significantly increased risks of VTE [OR 1.55 95% confidence interval (CI) 1.36, 1.76] and PE (OR 3.68, 95% CI 1.23, 11.05). Subgroup analyses suggested that new users were associated with a higher risk of VTE (OR 2.06, 95% CI 1.81, 2.35). For individual drugs, increased risk of VTE and PE was observed in taking haloperidol, risperidone, olanzapine, prochlorperazine but not in chlorpromazine, quetiapine or aripiprazole. However, careful interpretation is needed because of high heterogeneity among studies and scarce data. Conclusion: The present comprehensive meta-analysis further indicates a significantly increased risk of VTE and PE in current APS users compared with non-users. Subgroup analyses suggest that new users are more likely to develop VTE. However, due to significant heterogeneity among studies, conclusions should be considered with caution.